2017
DOI: 10.1104/pp.17.00638
|View full text |Cite
|
Sign up to set email alerts
|

A Violaxanthin Deepoxidase Interacts with a Viral Suppressor of RNA Silencing to Inhibit Virus Amplification

Abstract: RNA silencing plays a critical role against viral infection. To counteract this antiviral silencing, viruses have evolved various RNA silencing suppressors. Meanwhile, plants have evolved counter-counter defense strategies against RNA silencing suppression (RSS). In this study, the violaxanthin deepoxidase protein of maize (Zea mays), ZmVDE, was shown to interact specifically with the helper component-proteinase (HC-Pro; a viral RNA silencing suppressor) of Sugarcane mosaic virus (SCMV) via its mature protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 109 publications
2
37
0
Order By: Relevance
“…We used the Brome mosaic virus (BMV)‐derived virus‐induced gene silencing (VIGS) vector to knockdown ZmPAL transcript accumulation. BMV‐VIGS has been used successfully to decrease expression of specific maize genes for interaction studies of maize with fungal and viral pathogens (Cao et al ., ; Chen et al ., , ; van der Linde et al ., , ; Zhu et al ., ). Since the ten putative ZmPAL genes share high nucleotide sequence identity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the Brome mosaic virus (BMV)‐derived virus‐induced gene silencing (VIGS) vector to knockdown ZmPAL transcript accumulation. BMV‐VIGS has been used successfully to decrease expression of specific maize genes for interaction studies of maize with fungal and viral pathogens (Cao et al ., ; Chen et al ., , ; van der Linde et al ., , ; Zhu et al ., ). Since the ten putative ZmPAL genes share high nucleotide sequence identity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial efforts have been devoted to understanding the molecular interactions between maize and SCMV in order to develop sustainable maize protection strategies. For instance, several maize proteins have been identified that interact directly with SCMV‐encoded proteins (Chen et al ., ; Cheng et al ., ; Zhu et al ., ). Gene and protein expression profiling have also been conducted to elucidate the response of maize to SCMV infection (Chen et al ., ; Shi et al ., , ; Uzarowska et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VSRs have been regarded as a counter for plant defenses to facilitate viral infection ( Mathioudakis et al , 2013 ; Chen et al , 2017 ; Hafrén et al ., 2018 ). The VSR of Tomato yellow leaf curl China virus increased the expression of the tobacco calmodulin-like protein rgs-CaM to strengthen the activity of RSS ( Makiyama et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The violaxanthin deepoxidase protein of maize (Zea mays), ZmVDE binds with HC-Pro of SCMV and this interaction down-regulates the RNA silencing suppression activity of HC-Pro. This down-regulation results in reduced accumulation of viral RNA and coat-protein in the infected cell [25]. Examples can also be drawn from geminivirus infection in tobacco cells.…”
mentioning
confidence: 99%